IMPACT OF MODE OF DELIVERY ON EARLY INITIATION OF BREASTFEEDING AND EXCLUSIVE BREASTFEEDING AT DISCHARGE AMONG POSTNATAL MOTHERS: A HOSPITAL-BASED CROSS-SECTIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Breastfeeding is a cornerstone of infant nutrition and survival. Early initiation of breastfeeding within one hour of birth and exclusive breastfeeding for the first six months are recommended by the World Health Organization. Mode of delivery may significantly influence breastfeeding practices, particularly the timing of breastfeeding initiation. Objectives: To assess breastfeeding practices among postnatal mothers and evaluate the impact of mode of delivery on early initiation of breastfeeding and exclusive breastfeeding at discharge. Materials and Methods: A hospital-based cross-sectional study was conducted among 100 postnatal mothers delivering at a tertiary care teaching hospital. Maternal demographic characteristics, obstetric factors, neonatal characteristics, and breastfeeding practices were recorded using a structured questionnaire. Data were analyzed using descriptive statistics. Results: Among the study participants, 40% were aged 18–25 years, 35% were aged 25–30 years, 20% were aged 30–35 years, and 5% were aged 35–40 years. Seventy mothers underwent cesarean section while 30 delivered vaginally. Gestational diabetes mellitus and hypertension were present in 20% and 15% of mothers respectively. Among neonates, 90% were term and 10% were preterm. Birth weight ranged between 2.5 and 3.0 kg in 85% of newborns. Breastfeeding was initiated within one hour in 30% of mothers, after 4 hours in 50%, after 12 hours in 10%, while 10% had not initiated breastfeeding at the time of assessment. Colostrum feeding was practiced by 60% of mothers. Formula supplementation was given to 20% of infants. Lactation counselling was received by 90% of mothers. Exclusive breastfeeding at discharge was achieved in 90% of newborns. Conclusion: Despite a high prevalence of lactation counselling and exclusive breastfeeding at discharge, early initiation of breastfeeding remains suboptimal. High cesarean section rates may contribute to delayed breastfeeding initiation. Strengthening postnatal breastfeeding support and counselling may improve breastfeeding outcomes.